Risultati e significato della sorveglianza tubercolinica di base fra i lavoratori di un’azienda sanitaria ospedaliera esposti a rischio professionale / Results and significance of a baseline tuberculin skin test programme among health care workers in a hospital setting - Gerbaudo, L.; Violante, B. (La Medicina del Lavoro, 2007)
Una survey basata sull’esecuzione del test cutaneo con la tubercolina (TsT) è stata condotta su 2210 lavoratori esposti a rischio di Tb dell’azienda ospedaliera Santa Croce e Carle di Cuneo allo scopo di valutare gli indici di prevalenza di infezione tubercolare latente (ITL) e di individuare le variabili associate ad una risposta positiva del TsT. Il 12,4% (274/2210) dei soggetti sottoposti a screening ha evidenziato un TsT positivo. L’analisi multivariata condotta tramite test di regressione logistica ha mostrato che il sesso maschile, le classi di anzianità lavorativa più avanzate, l’appartenenza ad unità operative con livello più alto di rischio (limitato e medio), la mansione di operatore sanitario (ma non di medico), la provenienza da Paesi ad elevata prevalenza di Tb, la presenza di una storia clinica compatibile con Tb certa o sospetta, la vaccinazione con BCG, risultavano fattori significativamente associati ad una reazione positiva del TsT. Viceversa, le variabili anzianità anagrafica ed episodi di contatti stretti con pazienti a rischio di TB, che erano risultati in grado di discriminare fra le risposte tubercoliniche nell’analisi univariata preliminarmente condotta, si sono dimostrati fattori confondenti. In 17 soggetti (0,8%) la positività al TsT è stata ottenuta dopo un test two-step. Il fenomeno del boosting è stato trovato correlare positivamente con l’anzianità anagrafica e lavorativa e con la vaccinazione con BCG. L’elevata percentuale di soggetti che hanno aderito alle pratiche di sorveglianza tubercolinica (93,3%), è attribuibile, in buona misura, alle iniziative di formazione e informazione appositamente predisposte in Azienda. Results and significance of a baseline tuberculin skin test programme among health care workers in a hospital setting Background: Due to the resurgence of tuberculosis (Tb), health care workers (HCW) are considered at increased risk for Latent Tuberculosis Infection (LTI). According to the national guidelines health care facilities are required both to perform tuberculin skin tests (TsT) on all employees with potential occupational exposure to Tb and to analyze the results obtained. However, only a limited number of studies can be found in the literature reporting data of Tb prevalence in Italian hospitals. Objectives: The aim of this study was to determine the prevalence of and the relative risks for positive TsT among employees of the Hospital of Cuneo. Methods: After informed consent, a questionnaire and a TsT according to the Mantoux technique were administered to the 2368 employees of the hospital exposed to occupational risk for Tb. The variables considered for the univariate and multivariate analysis included several anthropometric, occupational and clinical factors Results: 274 of the 2210 employees who completed the screening programme had positive TsT (12.4%). Only one subject had been treated for active Tb. Factors significantly associated with a positive TsT were duration of employment (odds ratio [OR]:4.90, CI: 2.25-10.66, for length of employment 10-17 years; and OR: 8,77, CI: 3.53-21.81, for length >17 years; p<0.001); working in a Tb high-risk occupational setting (OR: 4.26, CI: 1.90-9.57 for level of “limited” risk and OR: 5.68, CI: 2.47-13.07 for level of “medium” risk; p<0.001); belonging to nurse or assistant nurse job categories (OR: 2.80, CI: 1.09-7.19; p<0.05); history of active or latent Tb infection (OR:11.54, CI: 5.54-24.06; p<0.001); birth in a foreign country (OR: 4.40, CI: 1.30-14.85; p=0.01); and BCG immunization (OR: 2.51, CI: 1.68-3.75; p<0.001). Seventeen subjects had a positive reaction after a two-step test (0.8%). Boosting occurred among elderly employees (mean age: 48,3±8.0 yrs), with long duration of employment (22,2±10,5 yrs), vaccinated with BCG (17/17). Conclusions: Our data suggest that a baseline survey based on TsT is useful to assess the prevalence of and risk factors for TLI in a health care setting. The high rate of participation in the survey (93.3%) was probably due to the training and awareness efforts aimed specifically at exposed HCW.